Drivers of Sustainable Rural Growth and Poverty Reduction in Central America : Honduras Case Study, Volume 2. Background Papers and Technical Appendices - World Bank (Washington, DC, 2013)
This regional study encompasses three Central American countries: Nicaragua, Guatemala, and Honduras. The focus of this report is Honduras. The objective of the study is to understand how broad-based economic growth can be stimulated and sustained in rural Central America. The study identifies "drivers" of sustainable rural growth and poverty reduction. Drivers are defined as the assets and combinations of assets needed by different types of households in different geographical areas, to take advantage of economic opportunities, and improve their well-being over time. The study examines the relative contributions of these assets, and seeks to identify the combinations of productive, social, and location-specific assets that matter most to raise incomes, and take advantage of prospects for poverty-reducing growth. It adopts an asset-based conceptual approach, where assets are defined to include natural, physical, financial, human, social, political, institutional, and location-specific assets, and, focuses on how households deploy their assets within the context of policies, institutions, and risks to generate a set of opportunities. The report further analyzes the quantity, quality, and productivity of assets needed by households in different geographical areas, to exercise their potential for generating long-term growth and improving well-being. Findings indicate that while there are well-defined areas of higher economic opportunity, given their underlying agricultural potential, relatively good access to infrastructure, and high population densities, poverty is widespread, and deep in rural Honduras, particularly in hillside areas. And, although agriculture should form an integral part of the rural growth strategy in hillside areas, despite its limited potential, agriculture alone cannot solve the rural poverty problem, yet, those remaining in the sector need to be more efficient, productive and competitive. It is recommended to move from geographically untargeted investments in single assets, to a more integrated and geographically based approach of asset enhancement with proper complementarities, such as land access and security, technical assistance provision, health and education services, and strong local level institutions,